Eye-closure increases children's memory accuracy for visual material - Mastroberardino, Serena; Vredeveldt, Annelies (Frontiers in Psychology, 2014)
Research shows that closing the eyes during retrieval can help both adults and children to remember more about witnessed events. In this study, we investigated whether the eye-closure effect in children is explained by general cognitive load, modality-specific interference, or a combination. 120 children (60 female) aged between 8 and 11 years viewed a 5-minute clip depicting a theft and were questioned about the event. During the cued-recall interview, children either viewed a blank screen (blank-screen condition), kept their eyes closed (eye-closure condition), were exposed to visual stimuli (visual-distraction condition), or were exposed to auditory stimuli (auditory-distraction condition). Children in the blank-screen and eye-closure conditions provided significantly more correct and fewer incorrect responses about visual details than children in the visual- and auditory-distraction conditions. No advantage was found for auditory details. These results support neither a pure cognitive-load explanation (in which the effect is expected to be observed for recall of both visual and auditory details), nor a pure modality-specific account (in which recall of visual details should only be disrupted by visual distractions). Practical implications of the findings are discussed.